2000
DOI: 10.1159/000056840
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing, chromosome assignment and subcellular localization of the testicular haploid expressed gene (THEG)

Abstract: We have previously isolated and characterized the mouse Testicular Haploid Expressed Gene (Theg) that is specifically expressed in haploid germ cells. We now describe the molecular cloning and characterization of the human homologue (THEG) of mouse Theg. Expression studies by using both dot blot and Northern blot techniques revealed that human THEG is expressed specifically in the testis. Additionally, we found two alternatively spliced transcripts (THEG major and THEG minor) for THEG by using reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…THEG is the human ortholog of mouse Theg (testicular haploid expressed gene) (6). RT-PCR and DNA sequencing indicated that both known splice variants of 379 and 344 aa are expressed in testis and in cancer.…”
Section: Mrna Expression Of Ct-candidate Genes In Normal Tissues and mentioning
confidence: 99%
“…THEG is the human ortholog of mouse Theg (testicular haploid expressed gene) (6). RT-PCR and DNA sequencing indicated that both known splice variants of 379 and 344 aa are expressed in testis and in cancer.…”
Section: Mrna Expression Of Ct-candidate Genes In Normal Tissues and mentioning
confidence: 99%
“…In previous coculture studies, expression of Theg was maintained at high levels in spermatids only in the presence of Sertoli cells [11]. Theg is predominantly expressed in the nucleus of spermatids [13].…”
Section: Discussionmentioning
confidence: 86%
“…When the cDNA and deduced amino acid sequences of Theg were compared with the GenBank/EMBL and EST databases, Theg was shown to encode a novel protein containing two putative nuclear localization signals (NLS) of SV40 large T antigen type [12], which suggests that Theg is a nuclear protein. In our recent study, we demonstrated by using a specific antibody against Theg that these NLSs in the Theg protein are functional and that Theg is localized predominantly in the nucleus of haploid round spermatid [13]. We also showed that green fluorescent protein-tagged Theg was mainly expressed in the nucleus of transfected NIH3T3 cells.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations